Vulnerability of House-wives Mothers: Gender Responsiveness in the Elimination of HIV/AIDS in Surakarta - Haryani, Tiyas Nur (Yayasan Jurnal Perempuan, 2015)
In 2013 and 2014 it is recorded that 42% of women and 58% of men are infected with HIV. So far government response to HIV / AIDS still maintains that men and women as the same entity. The highest group being infected with HIV / AIDS in Indonesia today is housewives with a number reached 6,539. In Surakarta, low-risk group housewives infected with HIV/AIDS—recorded 346 cases as of August 2014. The amount is higher when compared to HIV and AIDS in the group of Female Sex Workers (FSW)—recorded 154 cases. Government response to the low risk group of housewives are still minimal. Strategic National Action Plan (SRAN) HIV and AIDS 2010-2014, housewives with low risk have not yet been targeted. Policies at the level of local government, planning and implementation of HIV / AIDS are still focused on key populations and people living with HIV/AIDS to reduce the number of new cases while housewives are still unreached.